If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y = -2x + 11 Reorder the terms: 3y = 11 + -2x Solving 3y = 11 + -2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '3'. y = 3.666666667 + -0.6666666667x Simplifying y = 3.666666667 + -0.6666666667x
| 2+7x=4x+8 | | ln(10lnx)=4 | | 6a=-18 | | 18p^2-18=77p | | -9+-6y+6y=-9 | | (5x-12)+(3x-2)=180 | | 4p-3q=23 | | j+556=-7 | | 0.21x+252.00=850 | | 6+40=15x-50 | | 4x+70= | | ln(x-1)-ln(x+1)=2 | | 10x+15y=6 | | 0x+15y=6 | | 8d-(2+d)=42 | | 3p+2q=17 | | 8-7+3= | | 34.4*42= | | d-1-15=45 | | -8z-64=72 | | 2(7x+1)=58 | | b-718=115/6 | | 15Y+4=3Y-8 | | b-7-1/8=11-5/6 | | Y=sin^3(4x)cos(4x) | | 1.4*b=b+8 | | 3ab+6= | | -15+2n=73 | | 3(x+5)-6=x-7 | | -3n^2(-2n^5+5n-5)= | | 7x=-13 | | 12x+1y=94 |